A multi-material, multi-cell volume bioprinting method

CN122998472APending Publication Date: 2026-10-30GUANGZHOU MEDICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611374174.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,该技术方案的应用场景为挤出式3D打印制备骨修复支架,其交联方式为初级光交联、次级乙醇浸泡、三级钙离子处理的分步后处理工艺,完全不涉及体积光固化一体成型,也未采用水相分离机制实现材料自发分区,层间界面稳定性差,且挤出式打印过程中喷嘴的剪切力会显著降低细胞活性

Benefits of technology

1、突破单一材料瓶颈,实现体积生物打印的多材料、多细胞同步构建。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998472A_ABST
    Figure CN122998472A_ABST
Patent Text Reader

Abstract

The application discloses a multi-material and multi-cell volume bio-printing method, which comprises the following steps: providing at least two light-crosslinking hydrogel solutions with a double-water-phase separation characteristic, loading different cells respectively, and then sequentially injecting the solutions into a printing container; standing to form a spatial partition structure with a clear phase interface; and using a volume bio-printing technology to perform synchronous light-crosslinking solidification in a single light radiation mode, and setting a light attenuation compensation coefficient of each partition according to the light attenuation characteristic of different materials, so that the actual received light dose of each layer reaches a complete crosslinking threshold value. The application deeply integrates the water phase separation mechanism and the volume printing integrated forming technology, breaks through the limitation of traditional volume printing which can only construct a single material structure, can realize accurate partition arrangement of multi-material and multi-cell in a three-dimensional space, can guarantee a clear and stable interface between layers, can ensure a high cell survival rate, and can realize fast forming, thereby providing reliable technical support for constructing a three-dimensional tissue model.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of bioprinting technology, specifically to a multi-material, multi-cell volume bioprinting method. Background Technology

[0002] Bioprinting is a crucial technology for constructing living structures through additive manufacturing by manipulating cell-containing inks. Volumetric bioprinting (VBP), a recently emerging monolithic molding technology, can construct centimeter-scale three-dimensional structures within seconds to minutes, offering significant advantages such as rapid molding speed and minimal cell damage. However, current volumetric bioprinting technologies face a core bottleneck in practical applications: current bio-ink systems suitable for VBP are primarily limited to single-material systems, making it difficult to achieve spatial partitioning and simultaneous printing of multiple materials and cells. Natural tissues generally exhibit anisotropic heterogeneous structures, and their construction often requires the synergistic integration of multiple biomaterials and cell types. Single-volume printing material systems cannot meet this requirement, significantly limiting the application and expansion of volumetric bioprinting technology in the construction of complex tissues / organs.

[0003] In existing volumetric bioprinting technologies, Chinese patent application CN202410511464.2 discloses a low-concentration silk fibroin / methacrylamide gelatin bio-ink suitable for volumetric bioprinting and its preparation method. The technical solution includes methacrylamide gelatin (GelMA), silk fibroin (SF), ruthenium pyridine complex / sodium persulfate initiator, and solvent, wherein the mass percentage of silk fibroin is 0.5%-1.25%, and the mass percentage of GelMA is 0.6%-20%. The core objective of this invention is to solve the problem of sedimentation caused by excessively low viscosity of low-concentration silk fibroin ink during volumetric printing, leading to deformation and reduced resolution of the printed product. However, this technical solution focuses solely on a single ink system, pursuing the homogeneous stability of the ink's single phase, without addressing the construction of any multi-material systems or mentioning the potential application of aqueous phase separation in multi-material printing. In other words, this technical solution can only perform volumetric printing within the framework of a single material and a single cell type, and cannot achieve the construction of complex heterogeneous structures such as multi-material partitioning and multi-cell directional distribution.

[0004] Chinese patent application CN202610136513.8 discloses a 3D-printed composite bio-ink and bio-scaffold, which combines three materials: tussah silk fibroin (TSF), methacrylamide gelatin (GelMA), and nano-hydroxyapatite (nHA). However, this technology is applied to extrusion 3D printing for bone repair scaffolds. Its cross-linking process involves a stepwise post-processing step: primary photocross-linking, secondary ethanol immersion, and tertiary calcium ion treatment. It completely lacks volumetric photopolymerization and does not employ an aqueous separation mechanism to achieve spontaneous material partitioning. This results in poor interlayer interface stability, and the shear force of the nozzle during extrusion printing significantly reduces cell viability. Besides the aforementioned patent literature, traditional multi-material layer-by-layer printing technologies (such as extrusion and inkjet bioprinting), while capable of spatially distributing multiple materials, inevitably suffer from inherent problems such as interface disturbance, cross-contamination, and long printing times due to their layer-by-layer stacking method, failing to combine the high-efficiency, integrated molding advantages of volumetric bioprinting. Therefore, how to achieve high-precision three-dimensional structure construction of multiple materials and multiple cells in volumetric bioprinting, while ensuring the stability of the interfaces between different materials and the integrity of the structure, remains a technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0005] To address the aforementioned technical challenges, this invention utilizes the two-phase separation characteristics between different photocrosslinked hydrogel solutions, enabling the spontaneous formation of a spatially partitioned structure with a clear phase interface in the liquid state; subsequently, this spatially partitioned structure is cured through photocrosslinking. Specifically, this invention provides a multi-material, multi-cell volume bioprinting method, comprising the following steps: Ink Formulation and Cell Loading: At least two photocrosslinked hydrogel solutions are provided, wherein the at least two photocrosslinked hydrogel solutions have thermodynamically driven aqueous two-phase separation characteristics; different types of target cells are suspended in the at least two photocrosslinked hydrogel solutions respectively to prepare at least two cell-loaded bioinks accordingly; Spontaneous spatial partitioning: The at least two types of cell-carrying bio-inks are sequentially injected into the printing container and left to stand. The dual aqueous phase separation characteristics are utilized to allow each cell-carrying bio-ink to spontaneously form a spatial partitioning structure with a clear phase interface. Integrated photopolymerization molding: Using volumetric bioprinting technology, the spatial partition structure within the printing container is synchronously photocrosslinked and cured in a single light radiation mode; In the integrated photocuring molding step, the light attenuation compensation coefficient of each material partition is set according to the differences in the absorption and scattering characteristics of different materials to the light source, so that the actual light dose received inside each material partition after the light path penetrates reaches the energy threshold required for complete cross-linking.

[0006] Preferably, the at least two photocrosslinked hydrogel solutions are selected from any two or more of the following: silk fibroin solution (SF), methacrylamide gelatin solution (GelMA), and methacrylamide dextran solution (DexMA); the above materials have aqueous phase separation compatibility and can spontaneously form a stable interface in an aqueous system; wherein, methacrylamide gelatin and methacrylamide dextran each contain photosensitive methacrylamide groups on their molecular chains, and can achieve crosslinking and curing through free radical polymerization in the presence of a photoinitiator; the silk fibroin molecular chains are rich in tyrosine residues, and can achieve curing through photooxidative crosslinking to form dityrosine covalent bonds under the catalysis of a ruthenium / sodium persulfate photoinitiation system.

[0007] Preferably, the at least two photocrosslinked hydrogel solutions comprise a 3%-4% w / v silk fibroin solution, a 5%-7% w / v methacrylamide gelatin solution, and an 8%-10% w / v methacrylamide dextran solution; wherein the weight-average molecular weight of the silk fibroin is 50-120 kDa; the weight-average molecular weight of the methacrylamide gelatin is 60-100 kDa, and its degree of substitution (DS) for methacrylamide is 0.4-0.8; and the weight-average molecular weight of the methacrylamide dextran is 20-70 kDa, and its degree of substitution (DS) for methacrylamide is 0.3-0.6. Within the above concentration range, the three materials can form a clear and stable three-layer spatial partitioned structure under static conditions, with clear interlayer interfaces and no interdiffusion.

[0008] More preferably, the at least two photocrosslinked hydrogel solutions comprise a concentration of 4% w / v silk fibroin solution, 5% w / v methacrylamide gelatin solution, and 8% w / v methacrylamide dextran solution; wherein the weight-average molecular weight of silk fibroin is 80 kDa; the weight-average molecular weight of methacrylamide gelatin is 100 kDa, and its degree of substitution (DS) for methacrylamide is 0.6; and the weight-average molecular weight of methacrylamide dextran is 50 kDa, and its degree of substitution (DS) for methacrylamide is 0.5. This specific combination represents the optimal ratio determined through concentration gradient screening experiments. Under these conditions, the three-layer material exhibits the best delamination effect, achieving an optimal balance between structural strength and interfacial stability.

[0009] Preferably, the integrated photopolymerization molding step employs green light volumetric bioprinting, with a photopolymerization light source wavelength of 492-577nm, preferably 525nm; during printing, the printing light intensity of each layer of material is independently 60-80mW / cm². 2The printing time is 50-70 seconds independently. Compared with near-ultraviolet light, green light has a deeper tissue penetration depth and lower cell phototoxicity, enabling integrated photocuring and cross-linking of millimeter-thick materials without damaging the activity of the loaded cells; the wavelength range of 492-577nm covers the entire visible and green light bands, ensuring effective matching with the absorption spectrum of the ruthenium / sodium persulfate photoinitiator system.

[0010] Preferably, after the at least two photocrosslinked hydrogel solutions spontaneously form a spatial partitioning structure in the printing container, before volumetric bioprinting, a layer stability assessment step is included: different colored fluorescent markers are added to the at least two photocrosslinked hydrogel solutions, and after standing for at least 2 hours, the solidified layered structure is observed under fluorescence microscopy to confirm the clarity of the interfaces between the material layers. This step, as a quality control measure before printing, can intuitively assess the stability of the layered interfaces and the compatibility between materials, ensuring that the ink system is in an optimal layered state before each printing, thereby improving the printing success rate.

[0011] Preferably, the different types of target cells include at least two of the following: human immortalized keratinocytes, human dermal fibroblasts, human umbilical vein endothelial cells, or adipose-derived stem cells; the different types of target cells are distributed according to the material layers in the spatial partition structure to achieve spatial positioning of different target cells, and the cell density in each material layer is independently 1×10⁻⁶. 6 -5×10 6 Cells / mL. The above cell types cover the main cellular components of the epidermis, dermis, and subcutaneous tissue in skin tissue, meeting the cell requirements for constructing vascularized artificial skin models; 1×10 6 -5×10 6 A density range of cells / mL ensures uniform cell distribution within the printed material and sufficient intercellular interactions (e.g., signal transduction), which is beneficial for cell survival and functional expression within the material. The design of loading different cell types onto each material layer enables biomimetic simulation of tissue-cell spatial distribution.

[0012] Preferably, the photocrosslinking hydrogel solution further contains a photoinitiator, which is a ruthenium / sodium persulfate system comprising tris(2,2'-bipyridine)ruthenium(II) chloride and sodium persulfate. This photoinitiation system exhibits broadband absorption characteristics in the visible light region and good excitation response capability in the green light band (492-577 nm), enabling it to effectively initiate photocrosslinking reactions under the illumination conditions of green light volume printing. Simultaneously, this system also possesses good biocompatibility and water solubility, allowing its use in cell-containing systems without significant cytotoxicity.

[0013] Preferably, the printing container is made of borosilicate glass. Borosilicate glass has excellent optical transmittance (≥92% transmittance for green light) and chemical inertness, which can effectively prevent the printing container from scattering and absorbing the incident light path, ensuring the uniformity of the light field energy distribution in volume printing.

[0014] The beneficial effects are: 1. Break through the bottleneck of single materials and realize the simultaneous construction of multi-material and multi-cell bioprinting.

[0015] Existing volumetric bioprinting technologies are limited to single-ink systems, failing to meet the needs of constructing heterogeneous structures from natural tissues. This application deeply integrates the principle of aqueous phase separation with volumetric bioprinting technology, utilizing the two-aqueous-phase separation characteristics between various photocrosslinked hydrogel solutions to spontaneously form spatial partition structures with clear interfaces within the printing container. Combined with the integrated molding advantages of volumetric bioprinting, multi-material spatial layout and multi-cell directional loading are simultaneously completed in a single molding process within the same printing container. This fundamentally breaks through the existing technical paradigm of volumetric bioprinting, which can only print single materials, providing a precise biomimetic construction path for complex heterogeneous three-dimensional tissue models using multiple materials.

[0016] 2. The stability of multi-material interfaces is significantly improved through the synergistic mechanism of aqueous phase separation and integrated molding.

[0017] Traditional layer-by-layer printing techniques for constructing multi-material structures subject existing layers to physical compression or interfacial disturbance with each new layer, leading to blurred interlayer interfaces, material diffusion, and even structural collapse. This application addresses these issues in two ways: firstly, by utilizing the thermodynamic spontaneous process of aqueous phase separation, stable partitions with defined interfacial energies are formed between different hydrogel solutions, fundamentally suppressing interfacial mixing and diffusion; secondly, by employing a volumetric bioprinting integrated molding method, repeated physical disturbances to the layered interfaces are avoided. The synergistic effect of these two methods enhances the clarity of the interfaces and the structural integrity of the multi-material structure.

[0018] 3. Achieves biomimetic directional distribution of multiple cells in three-dimensional space with excellent cell compatibility.

[0019] This invention achieves precise, directional distribution of different cell types in three-dimensional space, consistent with the spatial arrangement of natural tissue, by loading different cell types onto different material layers and utilizing the spatial partitioning characteristics of aqueous phase separation. Experimental data show that the cell survival rate of each layer remained above 86% on day 7 of culture after printing, and the cells continued to proliferate during the 7-day culture period. This demonstrates that the material system has good cell compatibility, supports the long-term survival and functional expression of the loaded cells, and can provide key technical support for constructing artificial tissue models with physiological functions.

[0020] 4. High printing efficiency and minimal cell damage.

[0021] Compared to layer-by-layer printing techniques, which typically require tens of minutes to several hours, the volumetric bioprinting technology employed in this application can complete the construction of a three-dimensional structure within 50-70 seconds, significantly improving printing efficiency. Short printing time can substantially reduce the exposure time of cells in non-physiological environments outside the body, minimizing cumulative photo / thermal / mechanical damage. Simultaneously, the green light source exhibits lower phototoxicity compared to traditional near-ultraviolet curing methods, further ensuring that cells maintain a highly active state after printing.

[0022] 5. The material system has strong compatibility and a wide process window, which can be flexibly adapted to different tissue construction needs.

[0023] The aqueous phase separation strategy employed in this application exhibits broad compatibility with various material combinations, including SF, GelMA, and DexMA photopolymer hydrogels. By adjusting parameters such as material concentration and molecular weight, the layering effect and interfacial properties can be flexibly controlled. The wide process window allows this method to be customized according to the structural characteristics and mechanical requirements of different target tissues, meeting the construction needs of various application scenarios such as vascularized skin, tissue repair scaffolds, and organ models. Attached Figure Description

[0024] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a schematic diagram illustrating the preparation, phase behavior, and molecular interaction mechanism of the multi-component hydrogel in Example 1.

[0025] Figure 2 This is a comparison chart of the forward printing resolution of the three materials in Example 1, along with quantitative statistical results.

[0026] Figure 3 This is a comparison chart of the negative printing resolution of the three materials in Example 1, along with quantitative statistical results.

[0027] Figure 4 These are comparison photos of the structural model and the actual product obtained by combining any two materials in Example 1.

[0028] Figure 5 These are photos comparing the structural model and the actual product obtained from the three material combinations in Example 1.

[0029] Figure 6The images show the live / dead staining fluorescence micrographs of three different cells in the corresponding material layers in Example 4, demonstrating the survival status of HaCaT, HUVECs, and HDFs cells in their respective material layers.

[0030] Figure 7 A bar chart showing the quantitative statistical survival rate of three different cells on day 7 in the corresponding material layers of Example 4 shows that the cell survival rate in each material layer reached over 90%.

[0031] Figure 8 The graph shows the proliferation rate of three different cells cultured in the corresponding material layer in Example 4 on days 1, 4, and 7, indicating that the number of cells continues to increase with the extension of culture time. Detailed Implementation

[0032] The present invention will now be described in further detail with reference to specific embodiments, so that those skilled in the art can more clearly understand the present invention.

[0033] The following embodiments are for illustrative purposes only, but the scope of protection of this invention is not limited to these embodiments. Any adjustments, substitutions, or combinations of parameters made within the technical concept and numerical range of this invention are within the scope of protection of this invention. Based on the specific embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. The technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.

[0034] In the embodiments of this invention, unless otherwise specified, all raw material components are commercially available products well-known to those skilled in the art; in the embodiments of this invention, unless specifically specified, the technical means used are all conventional means well-known to those skilled in the art. Where specific experimental steps or conditions are not specified in the embodiments, they can be performed according to the conventional experimental steps or conditions described in the literature in this field. Where the manufacturers of reagents or instruments are not specified, they are all conventional reagent products that can be obtained commercially. In this invention, the term "aqueous two-phase separation characteristic" refers to the state in which, in a liquid system where multiple water-soluble polymers coexist, due to thermodynamic factors such as steric repulsion, hydrogen bond differences, and hydrophobic interactions between different polymer chain segments, the system cannot form a homogeneous single phase under specific concentration and temperature conditions, but spontaneously separates into two or more coexisting aqueous phases rich in different polymers. This characteristic differs from traditional oil-water immiscible systems, where each separated phase is a continuous aqueous phase, exhibiting good biocompatibility with the encapsulated cells. The term "synchronous photocrosslinking and curing in a single light radiation mode" refers to a process in which all three-dimensional model information is projected onto the printing container via computer during volumetric bioprinting, and the entire three-dimensional structure is cured and formed with only a single light field irradiation, unlike layer-by-layer printing which requires multiple stacking exposures. This mode avoids repeated mechanical disturbances to the formed interface caused by layer-by-layer curing, and is one of the key distinguishing features between this invention and existing technologies.

[0035] Raw materials for bio-ink: Silk fibroin (SF, purity ≥98%) is extracted from natural silkworm cocoons. The extraction method can be found in the master's thesis of Liu Junwei of Yancheng Institute of Technology, entitled "Extraction Process and Hydrogel Properties of Natural Silk Fiber". Different weight-average molecular weights of natural silk fibroin, such as 50kDa, 80kDa, and 120kDa, can be obtained by using dialysis bags of different specifications. Methacrylamide gelatin (GelMA, degree of methacrylation DS is 0.6), and GelMA with different weight-average molecular weights (such as 60kDa, 100kDa) can be provided by Suzhou Yongqinquan Intelligent Equipment Co., Ltd. Methacrylamide dextran (DexMA, degree of methacrylation DS is 0.5), and DexMA with different weight-average molecular weights (such as 20kDa, 50kDa, 70kDa) are all provided by Suzhou Yongqinquan Intelligent Equipment Co., Ltd. Polyethylene glycol diacrylate (PEGDA, 1000 Da) was supplied by Wuhan Lanabai Pharmaceutical Chemical Co., Ltd. Photoinitiator: Ruthenium(II) chloride (Ru, CAS No. 14323-06-9, purity ≥98%) and sodium persulfate (SPS, CAS No. 7775-27-1, analytical grade) were provided by AdvancedBioMatrix. Lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP), purity ≥98%, was provided by Suzhou Yongqinquan Intelligent Equipment Co., Ltd. Cells and cell culture media: Human immortalized keratinocytes (HaCaT), cell line, provided by Wuhan Pronosei Life Science Technology Co., Ltd. Human umbilical vein endothelial cells (HUVECs), cell line, provided by Wuhan Pronosei Life Science Technology Co., Ltd. Human dermal fibroblasts (HDFs), primary cells, provided by Wuhan Pronosei Life Science Technology Co., Ltd. Phosphate-buffered saline (PBS), cell culture medium, and trypsin-EDTA digestion solution, among other cell culture reagents, were all purchased from Gibco. Fluorescent markers: AF488, AF555, and AF647 are all commercially available products.

[0036] Equipment source: The following instruments and consumables were used: Green Light Volume Bioprinting System (Green Key Biotechnology, VBP-T200); Universal Testing Machine (Shanghai Baosheng, TA.XTC-18); Fluorescence Microscope (Guangzhou Mingmei Optoelectronic Technology, MF53-N); Stereo Microscope (Guangzhou Mingmei Optoelectronic Technology, MZ62); Microplate Reader (Shanghai Agilent, BioTek Synergy LX); Scanning Electron Microscope (Hitachi, TM4000Plus II, Japan); Spectrophotometer (Hach, DR6000, USA); and other commercially available instruments and consumables.

[0037] Example 1 This embodiment aims to verify the layering stability and integrated printing performance of the multi-material system of the present invention under optimized process parameters. Specifically, it includes the following steps: Step S1. Preparation of photocrosslinking hydrogel solution Using phosphate-buffered saline (PBS) as the solvent, three solutions were prepared: SF (4% w / v, weight-average molecular weight 80 kDa), GelMA (5% w / v, weight-average molecular weight 100 kDa, DS 0.6), and DexMA (8% w / v, weight-average molecular weight 50 kDa, DS 0.5). Ru / SPS photoinitiator was added to these three solutions, with a final concentration of 1 mM ruthenium(II) tris(2,2'-bipyridine)chloride and a final concentration of 10 mM sodium persulfate. After thorough dissolution, the solutions were filtered through a 0.22 μm sterile syringe filter for sterilization.

[0038] Step S2. Spontaneous Spatial Partitioning and Hierarchical Stability Assessment Different colored fluorescent markers (AF488, AF555, and AF647) were added to the three solutions respectively, and the solutions were mixed in pairs and in triplicate in transparent borosilicate glass bottles with equal volumes. The injection rate was controlled at 0.5-1.0 mL / min to avoid direct impact of the liquid flow on the lower liquid surface. After each layer was injected, it was allowed to stand for 5 minutes to allow the liquid surface to stabilize before injecting the next layer. After all layers were injected, the solution was allowed to stand at 25±2℃ for 2 hours to form a spatial partitioned structure using the two-phase separation characteristics: an SF layer (upper layer), a GelMA layer (middle layer), and a DexMA layer (lower layer). Fluorescence microscopy showed that the fluorescence signal at the interface of the three layers exhibited a step change with no obvious overlap, and the interface was clear and stable. Figure 1 As shown, Figure 1 This is a schematic diagram illustrating the preparation, phase behavior, and molecular interaction mechanism of the multi-component hydrogel in this embodiment.

[0039] Step S3. Measurement and setting of optical attenuation compensation coefficient The absorbance of SF solution (4% w / v), GelMA solution (5% w / v), and DexMA solution (8% w / v) at 525 nm was measured using a spectrophotometer, and the optical attenuation coefficient of each material was calculated according to the Beer-Lambert law. Taking the first material SF layer in the optical path as the reference, the optical attenuation compensation coefficient of each material layer in this embodiment was determined by accumulating layer by layer as follows: SF layer 0.08691 mm. -1 GelMA layer 0.07253 mm -1 DexMA layer 0.07423 mm -1 This ensures that after the light path penetrates, the actual light dose received by each material partition reaches the energy threshold required for complete cross-linking.

[0040] Step S4. Integrated photopolymerization molding The printed bottle was placed in the green light volumetric bioprinting system. The Z-axis coordinates of the CAD model were calibrated according to the actual liquid level: SF layer (0-2mm), GelMA layer (2-4mm), and DexMA layer (4-6mm). The projected light field was subjected to pixel-by-pixel energy correction according to the light attenuation compensation coefficient determined in step S3 (SF layer × 0.08691, GelMA layer × 0.07253, DexMA layer × 0.07423). The light source wavelength was set to 525nm, and the principal light intensity of each layer was 70mW / cm². 2 A single light radiation simultaneously completes the three-layer cross-linking and curing process in 60 seconds. For example... Figure 2 and Figure 3 As shown. Figure 2This is a comparison chart of the forward printing resolution of the three materials in this embodiment, along with quantitative statistical results; Figure 3 This is a comparison chart of the negative printing resolution of the three materials in this embodiment, along with quantitative statistical results. For example... Figure 4 and Figure 5 As shown. Figure 4 These are comparison photos of the structural models and actual objects obtained by combining any two materials in this embodiment. Figure 5 These are photos comparing the structural models obtained from the three material combinations in this embodiment with the actual physical results. The photos clearly show that the printed models have distinct layers and clear boundaries.

[0041] Example 2 The difference between this embodiment and Example 1 is that phosphate-buffered saline (PBS) was used as the solvent to prepare SF solution (3% w / v, weight-average molecular weight 50 kDa), GelMA solution (5% w / v, weight-average molecular weight 60 kDa, DS 0.6), and DexMA solution (8% w / v, weight-average molecular weight 20 kDa, DS 0.5), respectively. The light source wavelength was adjusted to 492 nm, and the principal light intensity of each layer was 60 mW / cm². 2 Printing time: 70 seconds. The light attenuation compensation coefficient was adjusted accordingly to 0.13467 mm for the SF layer. -1 GelMA layer 0.08894 mm -1 DexMA layer 0.09472 mm -1 The remaining operating steps are the same as in Example 1.

[0042] Example 3 The difference between this embodiment and Example 1 is that phosphate-buffered saline (PBS) was used as the solvent to prepare SF solution (4% w / v, weight-average molecular weight 120 kDa), GelMA solution (7% w / v, weight-average molecular weight 100 kDa, DS 0.6), and DexMA solution (10% w / v, weight-average molecular weight 70 kDa, DS 0.5), respectively. The light source wavelength was adjusted to 577 nm, and the principal light intensity of each layer was 80 mW / cm². 2 Printing time: 50 seconds. The light attenuation compensation coefficient was adjusted accordingly to 0.03062 mm for the SF layer. -1 GelMA layer 0.01428 mm -1 0.02471 mm DexMA layer -1 The remaining operating steps are the same as in Example 1.

[0043] Example 4 This embodiment uses the exact same material system and printing parameters as Example 1. The only difference is the addition of cell-carrying bio-ink preparation; the re-determination of the light attenuation compensation coefficient for the cell-carrying system; and the in vitro culture and cell performance testing steps. The remaining operations are the same as in Example 1. Details are as follows: 1. Preparation of cell-loaded bio-ink (new step) Human immortalized keratinocytes (HaCaT), human umbilical vein endothelial cells (HUVECs), and human dermal fibroblasts (HDFs) in the logarithmic growth phase were collected. Cells were digested with 0.25% trypsin-EDTA solution and centrifuged at 1000 rpm for 5 min to collect the cell pellet.

[0044] Using the 4% w / v SF solution, 5% w / v GelMA solution, and 8% w / v DexMA solution prepared in step S1 of Example 1, HaCaT, HUVECs, and HDFs cells were resuspended, respectively. The cells were gently pipetted 10-15 times to achieve uniform cell dispersion, and the cell density of each ink system was uniformly adjusted to 2 × 10⁻⁶. 6 Three cell-carrying bioinks, namely SF-HaCaT, GelMA-HUVECs, and DexMA-HDFs, were obtained by adding cells / mL. Differential fluorescent markers were added to each cell-carrying bioink for subsequent layered interface observation.

[0045] 2. Spontaneous spatial partitioning and integrated photopolymerization molding (same as Example 1) Using a pipette, the three cell-carrying inks were placed along the wall of a borosilicate glass printing bottle and allowed to stand. Utilizing the aqueous two-phase separation characteristic, a stable three-layer partitioned structure was formed, from top to bottom: SF-HaCaT layer (upper layer), GelMA-HUVECs layer (middle layer), and DexMA-HDFs layer (lower layer). After passing the fluorescence microscopy layer interface evaluation, the light attenuation compensation coefficient (SF-HaCaT layer 0.44798 mm) was re-determined according to the light attenuation compensation coefficient determination method in Example 1. -1 GelMA-HUVECs layer 0.30731 mm -1 0.35101 mm DexMA-HDFs layer -1 Complete Z-axis calibration of the printed model and pixel-by-pixel energy correction of the projected light field; using 525nm green light and 70mW / cm². 2 A single exposure of light intensity for 60 seconds completes the synchronous and integrated photopolymerization molding of a three-layer partitioned structure.

[0046] 3. In vitro culture and cell performance testing (new step) After curing, the 3D layered printed structure was removed and transferred to a 6-well culture plate containing complete cell culture medium. The plate was then placed in a 37°C, 5% CO2 incubator for long-term culture. Two assays were performed on days 1, 4, and 7 after printing. (1) Observation of live / dead cell fluorescence staining: Calcein-AM live cell dye and PI dead cell dye were used for staining in the dark. Fluorescence microscope was used for dual-channel imaging at 488nm and 570nm. ImageJ software was used to count the cell viability in each material layer. (2) Quantitative detection of CCK-8 cell proliferation: SF, GelMA and DexMA gel slices were cut into layers, incubated with CCK-8 reagent for 3h, and the absorbance was detected by microplate reader at 450nm. The relative cell proliferation rate at each time point was calculated based on the number of cells at the initial printing time.

[0047] like Figures 6 to 8 As shown, Figure 6 The images shown are fluorescence micrographs of the corresponding material layers in this embodiment, illustrating the survival status of HaCaT, HUVECs, and HDFs cells in their respective material layers. Figure 7 A bar chart showing the quantitative statistical results of the cell viability on day 7 of culture in the corresponding material layers of the three different cell types in this embodiment shows that the cell viability in each material layer reached over 90%. Figure 8 The graph shows the proliferation rate of three different cell types on days 1, 4, and 7 of culture in the corresponding material layer in this embodiment, indicating that the number of cells continues to increase with the extension of culture time.

[0048] Example 5 The only difference between this embodiment and Embodiment 4 is that the material system and printing parameters of Embodiment 2 are used to verify the construction effect of the lower limit cell density, and the light attenuation compensation coefficient of the cell-loaded system is re-measured, as follows: Using the 3% w / v SF solution, 5% w / v GelMA solution, and 8% w / v DexMA solution prepared in Example 2, HaCaT, HUVECs, and HDFs cells were resuspended, respectively. Cells were gently pipetted 10-15 times to achieve uniform cell dispersion, and the cell density of each ink system was uniformly adjusted to 1×10⁻⁶. 6 Three cell-carrying bio-inks were obtained by using cells / mL: SF-HaCaT, GelMA-HUVECs, and DexMA-HDFs. The optical attenuation compensation coefficient (SF-HaCaT layer 1.03813 mm) was re-determined according to the optical attenuation compensation coefficient measurement method in Example 1. -1 GelMA-HUVECs layer 0.81504 mm -1 0.93420 mm DexMA-HDFs layer -1 Complete Z-axis calibration of the printed model and pixel-by-pixel energy correction of the projected light field; using 492nm green light and 60mW / cm². 2A single exposure of 70 seconds completes the synchronous integrated photopolymerization molding of the three-layer partitioned structure. All other operation steps are the same as in Example 4.

[0049] Example 6 The only difference between this embodiment and Embodiment 4 is that the material system and printing parameters of Embodiment 3 are used to verify the construction effect of the upper limit cell density. The light attenuation compensation coefficient of the cell-loaded system is re-measured, as follows: Using the 4% w / v SF solution, 7% w / v GelMA solution, and 10% w / v DexMA solution prepared in Example 3, HaCaT, HUVECs, and HDFs cells were resuspended, respectively. Cells were gently pipetted 10-15 times to achieve uniform cell dispersion, and the cell density of each ink system was uniformly adjusted to 5 × 10⁻⁶. 6 Three cell-carrying bio-inks were obtained by using cells / mL: SF-HaCaT, GelMA-HUVECs, and DexMA-HDFs. The optical attenuation compensation coefficient (SF-HaCaT layer 0.18822 mm) was re-determined according to the optical attenuation compensation coefficient determination method in Example 1. -1 0.12551 mm GelMA-HUVECs layer -1 0.14536 mm DexMA-HDFs layer -1 Complete Z-axis calibration of the printed model and pixel-by-pixel energy correction of the projected light field; using 577nm green light and 80mW / cm². 2 A single 50-second light exposure completes the synchronous, integrated photopolymerization molding of the three-layer partitioned structure. All other operational steps are the same as in Example 4.

[0050] Comparative Example 1 The difference between this comparative example and Example 1 is that no optical attenuation compensation coefficient is set for each material layer; that is, all three materials use a uniform 70mW / cm². 2 Printing is performed using light intensity, without using an SF layer (0.08691 mm). -1 GelMA layer 0.07253 mm -1 0.07423 mm DexMA layer -1 The compensation coefficient. The remaining operating steps are the same as in Example 1.

[0051] Comparative Example 2 The difference between this comparative example and Example 1 is that 8% w / v PEGDA solution (1000 Da, prepared with PBS as solvent) was used instead of 8% w / v DexMA solution, and it was mixed in equal volumes with 4% w / v SF solution (80 kDa) and 5% w / v GelMA solution (100 kDa, DS 0.6) in a transparent borosilicate glass bottle. All other operating steps were the same as in Example 1.

[0052] Comparative Example 3 The difference between this comparative example and Example 4 is that the same three material systems and cell loading scheme as Example 4 are used, but traditional extrusion bioprinting technology is used instead of volumetric bioprinting. The specific steps are as follows: the three cell-carrying inks are loaded into three cartridges respectively, and extruded layer by layer according to the design model. After each layer is printed, near-ultraviolet light pre-crosslinking is performed (wavelength 405nm, light intensity 30mW / cm²). 2 (Time 10s, photoinitiation system is the same as in Example 4), after all layers are stacked, final crosslinking is performed (green light 525nm, light intensity 70mW / cm²). 2 The printing time was 60 seconds (the photoinitiation system was the same as in Example 4). The total printing time was 45 minutes. All other operating steps were the same as in Example 4.

[0053] Comparative Example 4 The difference between this comparative example and Example 4 is that near-ultraviolet light (wavelength 405nm) was used instead of green light for volumetric bioprinting, and the photoinitiator was replaced with lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP, concentration 2mM). Following the same method as in Example 1, the absorbance of three LAP-containing cell-carrying inks at 405 nm was measured, and the light attenuation compensation coefficients for each material partition were calculated and set (SF-HaCaT layer 2.5, GelMA-HUVECs layer 1.8, DexMA-HDFs layer 1.6). Z-axis calibration of the printed model and pixel-by-pixel energy correction of the projected light field were completed. The printing light intensity was adjusted to 30mW / cm². 2 The printing time is 90 seconds. A quartz glass bottle is used as the printing container. All other operating steps are the same as in Example 4.

[0054] Test Example 1 Test objects: The materials of Examples 1-3 and Comparative Example 1 were printed and cured into cylindrical specimens with identical dimensions and layered structures (specimen diameter 8mm, height 6mm, single layer height 2mm).

[0055] Printing resolution test: After printing each material layer in each embodiment, the minimum formable feature size (positive direction) and the minimum retainable aperture (negative direction) were observed and measured using a stereomicroscope. Three different field-of-view measurements were taken for each model and the average value was calculated.

[0056] Compression modulus: The cylindrical specimens were subjected to compression tests using a universal testing machine at a compression rate of 1 mm / min. The stress-strain curves were recorded and the compression modulus was calculated.

[0057] Degradation performance: The solidified material samples were placed in PBS solution containing collagenase (1U / mL) and cultured at 37℃ with shaking. The solution was replaced with fresh solution every 24 hours. After 7 days, samples were taken, lyophilized, and the remaining mass was weighed to calculate the mass loss rate.

[0058] Geometric similarity: Measure the actual dimensions of the printed model in each dimension and calculate the geometric similarity with the CAD design model.

[0059] Interlayer interface clarity rating: Five technicians conducted a blind evaluation of the interlayer interface clarity using a scale of 1-10 (10 being the clearest). The test results are shown in Table 1.

[0060] Table 1. Performance test results of printed samples obtained from each embodiment and comparative example ( ±s, n=3) As shown in Table 1, the overall performance indicators of Examples 1 to 3 are superior to those of Comparative Examples 1 and 2, indicating that the preferred optical attenuation compensation strategy and material combination of the present invention can effectively ensure the structural accuracy, mechanical integrity, and interface stability of multi-material volume printing. Specifically, the three material layers in Examples 1-3 all achieved high positive / negative resolution and geometric similarity, with interlayer interface clarity scores all exceeding 8.0, and the compressive modulus and degradation rate exhibited material-dependent differences.

[0061] Comparative Example 1 did not set light attenuation compensation coefficients for each material layer, and its layer resolution, geometric similarity, and interface clarity were significantly lower than those of the Example. This may be because different materials have inherent differences in their absorption and scattering capabilities for 525nm green light. If energy compensation is not performed according to the light attenuation characteristics of different materials, the actual light dose received by the deeper materials will be lower than the crosslinking threshold, resulting in insufficient crosslinking; at the same time, the upper materials may undergo excessive crosslinking due to excessive dose, causing distortion and interface blurring. The lack of light attenuation compensation coefficients causes the light field energy to decay rapidly along the light path, and the actual crosslinking density of each layer deviates from the design threshold, thereby reducing the overall printing resolution and interlayer interface clarity. In addition, the insufficiently crosslinked layer regions also showed lower mechanical modulus and higher mass loss rate in subsequent compression tests and degradation experiments. This may be because the incompletely crosslinked molecular chains cannot form a dense network structure, which weakens their ability to withstand external forces and makes them more susceptible to enzymatic degradation.

[0062] Comparative Example 2 used an 8% w / v PEGDA solution instead of an 8% w / v DexMA solution, blended with SF and GelMA solutions. The results showed that the interlayer interface clarity score was only around 5.2, far lower than the levels of the examples, and the geometric similarity was less than 70%, with significantly worse positive and negative resolution. This may be because PEGDA lacks sufficient thermodynamically driven aqueous phase separation between SF and GelMA, and the mixture tends to form a metastable or incompletely phase-separated state, making it difficult to spontaneously form a clear and stable macroscopic phase interface. The flexibility and hydrophilicity of the PEGDA molecular chain are relatively similar to the interaction parameters of SF and GelMA, failing to produce a strong repulsive phase separation effect similar to that in the DexMA system, leading to interdiffusion and interface blurring during standing. Furthermore, PEGDA does not contain naturally derived peptide or sugar structures, and its compatibility with the ruthenium / sodium persulfate photoinitiation system may be weak. Its photocrosslinking reaction kinetics are mismatched with SF and GelMA, resulting in asynchronous gelation during synchrotron radiation curing, further damaging the integrity of the partitioned structure. Therefore, the geometric similarity and interface clarity of Comparative Example 2 are significantly lower than those of the embodiment using the DexMA system in this invention, verifying the scientific nature and irreplaceability of the specific material combination of this invention.

[0063] Test Example 2 Test subjects: Examples 4 to 6, and Comparative Examples 2 and 3.

[0064] Cell viability: On day 7 of culture, the printed models containing different cells from each example and comparative example were removed from the well plates, gently rinsed with PBS, and then cut into thin slices along the interfaces of each material. Staining working solution containing Calcein-AM (2 μm) and propidium iodide (PI, 4 μm) was added, and the samples were incubated at 37°C for 30 min in the dark. After rinsing with PBS, images were observed and acquired using a fluorescence microscope in the 488 nm (green, live cells) and 570 nm (red, dead cells) channels. Cell counting was performed using ImageJ software, and cell viability was calculated.

[0065] Cell proliferation rate: The printed models of each example and comparative example were removed from culture on days 1, 4, and 7. After being cut along the material interface, the thin films of each material layer were transferred to 48-well plates. A culture medium mixture containing 1% (v / v) CCK-8 reagent was added to each well, and the plates were incubated at 37°C and 5% CO2 for 3 hours. 100 μL of the supernatant was transferred to a 96-well plate, and the absorbance was measured at 450 nm using a microplate reader. The relative proliferation rate on days 1, 4, and 7 was calculated with day 0 (the day the cell printing was completed) as the baseline. The test results are shown in Table 2.

[0066] Table 2. Results of cell viability testing of cell-printed samples obtained from each embodiment and comparative example ( ±s, n=3) Table 2 shows that the cell-printed models in Examples 4 to 6 exhibited a cell survival rate greater than 80% at day 7 of culture, and the cell proliferation rate showed a significant increasing trend with culture time. This indicates that the method of the present invention has good biocompatibility for different cell types and can support long-term cell survival and functional expression within a three-dimensional partitioned structure. Example 5 (cell density 1×10⁻⁶) 6 The cells (5 × 10⁶ cells / mL) exhibited higher survival and proliferation rates on day 7. This may be because the lower cell density facilitates the full diffusion of nutrients and the timely removal of metabolic waste, reducing competitive inhibition between cells. Simultaneously, the lower cell density has less impact on light scattering and thermal effects during photocrosslinking, thus reducing physical damage to cells during curing. Example 6 (cell density 5 × 10⁶ cells / mL) 6 Although the cell survival rate and proliferation rate of the high-density cell population on day 7 were slightly lower than those in Examples 4 and 5, they were still at an acceptable level. This may be because the high-density cell population scatters the incident light more during the photocuring process, resulting in slight fluctuations in the local actual light dose. At the same time, the high-density cells metabolize faster, and the changes in pH and oxygen partial pressure of the local microenvironment in the early stage may have a temporary impact on the cell adaptation period, but the system as a whole still has a good cell compatibility window.

[0067] Comparative Example 3 used traditional extrusion bioprinting technology instead of volumetric bioprinting. The cell survival rate of each layer in this example was significantly lower on day 7 than in the previous example, and the cell proliferation rate showed a decreasing trend over time, indicating that cells failed to proliferate effectively within the structure and even experienced activity decline. This may be because the high shear force applied by the nozzle to the cell-containing ink during extrusion printing directly damages the cell membrane, causing some cells to lose activity or be in a sublethal state at the beginning of printing. Furthermore, the layer-by-layer stacking printing method takes up to 45 minutes, significantly increasing the cumulative exposure time of cells to a non-physiological environment, exacerbating oxidative stress and metabolic disorders. More importantly, the deposition of each new layer of material during extrusion printing exerts physical pressure on the already solidified lower layer, causing micro-displacement and cell migration at the interlayer interface. This repeated mechanical disturbance not only disrupts the original spatial positioning of the cells but may also cause shear and compression damage at the interface, making it difficult for cells to recover and proliferate in subsequent culture. Therefore, although the material system and cell loading scheme are the same as in the previous example, the fundamental difference in the printing process leads to a huge difference in cell activity.

[0068] Comparative Example 4 used near-ultraviolet light (405 nm) instead of green light and LAP photoinitiator instead of the ruthenium / sodium persulfate system. To ensure that the actual light dose received by each material partition after near-ultraviolet light penetration reached the energy threshold required for complete cross-linking, appropriate light attenuation compensation coefficients were set for each material layer. However, the cell survival rate in Comparative Example 4 still dropped below 80% on day 7, and the proliferation rate showed a negative growth trend, indicating that a large number of cells died and could not proliferate. This shows that even under cross-linking conditions with uniform energy distribution, the combination of near-ultraviolet light and LAP photoinitiator still has a lethal damaging effect on cells. This may be because the highly reactive alkyl radicals generated by the cleavage of LAP under 405 nm near-ultraviolet light excitation have inherent cytotoxicity far exceeding that of the ruthenium / sodium persulfate system; at the same time, the high energy of near-ultraviolet light photons can directly induce the formation of DNA pyrimidine dimers, causing irreversible damage to genetic material, which manifests as a continuous decline in survival rate in the later stages of culture.

[0069] It is noteworthy that even under the dual physical challenges of extrusion shear force and intermittent ultraviolet irradiation, the cell survival rate of Comparative Example 3 on day 7 was still significantly higher than that of Comparative Example 4, indicating that the type of initiator may have a much greater impact on cell survival than simple physical shear force or photon irradiation.

[0070] In summary, the technical solution of this invention, through the rational selection of a combination of aqueous two-phase separation materials, the setting of a layer-by-layer light attenuation compensation coefficient, the use of a low-cytotoxic green ruthenium / sodium persulfate photoinitiation system, and the leveraging of the integrated rapid prototyping advantages of volumetric bioprinting, significantly improves the long-term activity and proliferation capacity of the loaded cells while ensuring the precision of the multi-material structure, demonstrating the comprehensive beneficial effect of the synergistic effect of multiple technical elements.

[0071] The above are merely embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of the claims of the present invention.

Claims

1. A multi-material, multi-cell volume bioprinting method, characterized in that, Includes the following steps: Ink Formulation and Cell Loading: At least two photocrosslinked hydrogel solutions are provided, wherein the at least two photocrosslinked hydrogel solutions have thermodynamically driven aqueous two-phase separation characteristics; different types of target cells are suspended in the at least two photocrosslinked hydrogel solutions respectively to prepare at least two cell-loaded bioinks accordingly; Spontaneous spatial partitioning: The at least two types of cell-carrying bio-inks are sequentially injected into the printing container and left to stand. The dual aqueous phase separation characteristics are utilized to allow each cell-carrying bio-ink to spontaneously form a spatial partitioning structure with a clear phase interface. Integrated photopolymerization molding: Using volumetric bioprinting technology, the spatial partition structure within the printing container is synchronously photocrosslinked and cured in a single light radiation mode; In the integrated photocuring molding step, the light attenuation compensation coefficient of each material partition is set according to the differences in the absorption and scattering characteristics of different materials to the light source, so that the actual light dose received inside each material partition after the light path penetrates reaches the energy threshold required for complete cross-linking.

2. The printing method according to claim 1, characterized in that, The at least two photocrosslinked hydrogel solutions are selected from any two or more of the following: silk fibroin solution, methacrylamide gelatin solution, and methacrylamide dextran solution.

3. The printing method according to claim 2, characterized in that, The at least two photocrosslinked hydrogel solutions include a 3%-4% w / v silk fibroin solution, a 5%-7% w / v methacrylamide gelatin solution, and an 8%-10% w / v methacrylamide dextran solution; wherein the weight-average molecular weight of the silk fibroin is 50-120 kDa; the weight-average molecular weight of the methacrylamide gelatin is 60-100 kDa; and the weight-average molecular weight of the methacrylamide dextran is 20-70 kDa.

4. The printing method according to claim 2, characterized in that, The at least two photocrosslinked hydrogel solutions include a 4% w / v silk fibroin solution, a 5% w / v methacrylamide gelatin solution, and an 8% w / v methacrylamide dextran solution; wherein the weight-average molecular weight of the silk fibroin is 80 kDa; the weight-average molecular weight of the methacrylamide gelatin is 100 kDa; and the weight-average molecular weight of the methacrylamide dextran is 50 kDa.

5. The printing method according to claim 1, characterized in that, The integrated photopolymerization molding step employs green light volumetric bioprinting, with a photopolymerization light source wavelength of 492-577nm; during printing, the printing light intensity of each layer of material is independently 60-80mW / cm². 2 The printing time is 50-70 seconds independently.

6. The printing method according to claim 1, characterized in that, Before performing the volumetric bioprinting, after the at least two photocrosslinked hydrogel solutions spontaneously form a spatial partition structure in the printing container, a layer stability assessment step is also included: different colored fluorescent markers are added to the at least two photocrosslinked hydrogel solutions respectively, and after standing for at least 2 hours, the solidified layered structure is observed by fluorescence microscopy to confirm the clarity of the interface between each material layer.

7. The printing method according to claim 1, characterized in that, The different types of target cells include at least two of the following: human immortalized keratinocytes, human dermal fibroblasts, human umbilical vein endothelial cells, or adipose-derived stem cells; the different types of target cells are distributed according to the material layers in the spatial partition structure to achieve spatial positioning of different target cells, and the cell density in each material layer is independently 1×10⁻⁶. 6 -5×10 6 per mL.

8. The printing method according to claim 1, characterized in that, The photocrosslinked hydrogel solution also contains a photoinitiator, which is a ruthenium / sodium persulfate system, including tris(2,2'-bipyridine)ruthenium(II) chloride and sodium persulfate.

9. The printing method according to claim 1, characterized in that, The printing container is made of borosilicate glass.

Citation Information

Patent Citations

  • Low-concentration silk fibroin / methacrylated gelatin bio-ink suitable for volume bio-printing as well as preparation method and application of low-concentration silk fibroin / methacrylated gelatin bio-ink

    CN118490888A

  • 3D printing composite bio-ink, biological scaffold and preparation method thereof

    CN121944247A